Ontogeny of pup isolation-induced ultrasonic calls in a highly social rodent, the Harting’s vole (Microtus hartingi) - Rutovskaya, Marina V.; Volodin, Ilya A.; Golenishchev, Fedor N.; Volodina, Elena V. (Behavioural processes, 2025)
We examined the ontogeny of pup ultrasonic isolation-induced calls (USVs) in a highly social Arvicolinae rodent species, the Harting’s vole (Microtus hartingi). We recorded, with two-days intervals, the USVs of 55 individual pups from 11 litters from 1 to 12 days of age and measured body mass and the linear body size variables of each subject. The number of pups producing USVs decreased from 100 % at 1–2 days of age to 11.5 % at 11–12 days of age. Call rate changed with age, with maximum at 3–4 d of age. It ranged from 121.8 to 94.2 USVs/min between 1–2 and 7–8 days of age, decreased to 36.4 USVs/min at 9–10 days of age and to 1.5 USVs/min at 11–12 days of age. Overall, pup USVs were becoming simpler in their contour shapes with increase of age. Pup age class significantly affected all acoustic variables for the exclusion of the start and maximum fundamental frequencies, which values did not display significant changes with age. Body mass negatively correlated with USV acoustic variables, for the exclusion of call rate. A high percent of USVs contained nonlinear phenomena. We discuss the differences and similarities of pup Harting’s vole USV ontogeny with other vole species and summarize the traits which make pup USVs of the Harting’ vole a convenient model for biomedical research. •We investigated ontogeny of pup ultrasonic isolation calls in the Harting's vole.•Pup call rates were high during first 8 days of age, then calling activity decreased.•Pup age affected all acoustic variables aside from two frequency parameters.•A high percent of ultrasonic calls contained nonlinear phenomena.•Body mass negatively correlated with acoustic variables, aside from call rate.